Insect frass fertilizer as a regenerative input for improved biological nitrogen fixation and sustainable bush bean production - Chepkorir, Agnes; Beesigamukama, Dennis; Gitari, Harun I.; Chia, Shaphan Y.; Subramanian, Sevgan; Ekesi, Sunday; Abucheli, Birachi Eliud; Rubyogo, Jean Claude; Zahariadis, Theodore; Athanasiou, Gina; Zachariadi, Aikaterini; Zachariadis, Vasileios; et al. (Frontiers in Plant Science, 2024)
Bush bean (Phaseolus vulgaris L.) production is undermined by soil degradation and low biological nitrogen fixation (BNF) capacity. This study evaluated the effect of black soldier fly frass fertilizer (BSFFF) on bush bean growth, yield, nutrient uptake, BNF, and profitability, in comparison with commercial organic fertilizer (Phymyx, Phytomedia International Ltd., Kiambu, Kenya), synthetic fertilizer (NPK), and rhizobia inoculant (Biofix, MEA Fertilizers, Nairobi, Kenya). The organic fertilizers were applied at rates of 0, 15, 30, and 45 kg N ha -1 while the NPK was applied at 40 kg N ha -1 , 46 kg P ha -1 , and 60 kg K ha -1 . The fertilizers were applied singly and in combination with rhizobia inoculant to determine the interactive effects on bush bean production. Results showed that beans grown using BSFFF were the tallest, with the broadest leaves, and the highest chlorophyll content. Plots treated with 45 kg N ha -1 BSFFF produced beans with more flowers (7 -8 %), pods (4 -9%), and seeds (9 -11%) compared to Phymyx and NPK treatments. The same treatment also produced beans with 6, 8, and 18% higher 100-seed weight, compared to NPK, Phymyx, and control treatments, respectively. Beans grown in soil amended with 30 kg N ha -1 of BSFFF had 3-14-fold higher effective root nodules, fixed 48%, 31%, and 91% more N compared to Phymyx, NPK, and rhizobia, respectively, and boosted N uptake (19 -39%) compared to Phymyx and NPK treatments. Application of 45 kg N ha -1 of BSFFF increased bean seed yield by 43%, 72%, and 67% compared to the control, NPK and equivalent rate of Phymyx, respectively. The net income and gross margin achieved using BSFFF treatments were 73 -239% and 118 -184% higher than the values obtained under Phymyx treatments. Our findings demonstrate the high efficacy of BSFFF as a novel soil input and sustainable alternative for boosting BNF and improving bush bean productivity.